2022
DOI: 10.1021/acs.est.1c05170
|View full text |Cite
|
Sign up to set email alerts
|

Dehalogenation of Polybrominated Diphenyl Ethers and Polychlorinated Biphenyls Catalyzed by a Reductive Dehalogenase in Dehalococcoides mccartyi Strain MB

Abstract: Polybrominated diphenyl ethers (PBDEs) and polychlorinated biphenyls (PCBs) are notorious persistent organic pollutants. However, few organohalide-respiring bacteria that harbor reductive dehalogenases (RDases) capable of dehalogenating these pollutants have been identified. Here, we report reductive dehalogenation of penta-BDEs and PCBs byDehalococcoides mccartyi strain MB. The PCE-pregrown cultures of strain MB debrominated 86.6 ± 7.4% penta-BDEs to di- to tetra-BDEs within 5 days. Similarly, extensive dechl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Microbial reductive dehalogenation performed by organohalide-respiring bacteria (OHRB) is the major process attenuating organohalide pollutants in anaerobic environments. , Reductive debromination of penta-BDEs was reported in only a few Acetobacterium , Dehalobacter , and Dehalococcoides isolates and microcosms. ,, Unfortunately, most reported isolates and microcosms only partially debrominated penta-BDEs to less brominated but more toxic PBDE congeners ( e.g. , di- to tetra-BDEs). ,, Only two D. mccartyi strains ( i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial reductive dehalogenation performed by organohalide-respiring bacteria (OHRB) is the major process attenuating organohalide pollutants in anaerobic environments. , Reductive debromination of penta-BDEs was reported in only a few Acetobacterium , Dehalobacter , and Dehalococcoides isolates and microcosms. ,, Unfortunately, most reported isolates and microcosms only partially debrominated penta-BDEs to less brominated but more toxic PBDE congeners ( e.g. , di- to tetra-BDEs). ,, Only two D. mccartyi strains ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,14−18 Unfortu-nately, most reported isolates and microcosms only partially debrominated penta-BDEs to less brominated but more toxic PBDE congeners (e.g., di-to tetra-BDEs). 14,15,18 Only two D. mccartyi strains (i.e., GY50 and TZ50) could completely debrominate penta-BDEs to diphenyl ether, 11,16 but the reductive dehalogenase (RDase) genes responsible for complete debromination were easily lost when cultivated with alternative organohalide substrates. 11,16 More recently, D. mccartyi strain CG1, which has been cultivated with tetrachloroethene (PCE), was implicated to debrominate penta-BDEs to diphenyl ether, making it a potential candidate for bioremediation of PBDEs-contaminated sites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In other PCB dehalogenation studies using transcriptomics, the Dehalococcoides cell density was several orders of magnitude higher than that in our study. Thus, a wide range of RDase gene expression from Dehalococcoides genomes was detected, but only those that were significantly expressed were identified as PCB dehalogenase genes. ,,, Here, RNA was extracted from microcosms that were far less enriched for Dehalococcoides . It is possible that other RDase genes were expressed in HPCBM at levels that were undetectable by metatranscriptomic sequencing despite the robust sequencing coverage (45–71 million sequences per sample).…”
Section: Resultsmentioning
confidence: 99%
“…An OHRB genus of particular interest and relevance, Dehalococcoides , contains members that can grow with PCBs as an electron acceptor, hydrogen as an electron donor, and acetate as a carbon source. , The key enzymes for organohalide respiration by Dehalococcoides are reductive dehalogenases (RDases) which contain a corrinoid cofactor involved in catalysis . RDases for PCB dechlorination identified from Dehalococcoides so far are bifunctional, catalyzing both PCB and tetrachloroethene (PCE) reduction, suggesting that precultivation with PCE would be a useful strategy for growing active biomass as PCB-dechlorinating Dehalococcoides are otherwise difficult to enrich. Because Dehalococcoides lead specialized lifestyles, their genomes are streamlined and lack many complete pathways to produce required substrates and cofactors (e.g., corrinoids) and metabolize harmful intermediates (e.g., carbon monoxide (CO)). These factors drive important interactions with microbial community members, as evidenced by syntrophic relationships found between Dehalococcoides mccartyi and hydrogen, acetate, and corrinoid producers and CO oxidizers. Sequencing technology advances have facilitated studies of interactions between Dehalococcoides and other microbes in PCB-contaminated marine sediments and enrichment cultures. ,,,, Further deciphering the interactions between Dehalococcoides and indigenous microorganisms is important to improve and optimize halogenated pollutant bioremediation strategies, such as maintaining growth and reductive dechlorination activity of Dehalococcoides at contaminated sites.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, a natural attenuation process, microbial reductive dechlorination, detoxifies PCBs via replacing chlorine substituents with hydrogen in a stepwise way, offering a promising and green technique for PCB removal. 5 So far, it has been shown that anaerobic species, including Dehalococcoides mccartyi strains 195, 6 CBDB1, 7 JNA, 8 CG1, CG4, CG5 9 and MB, 10 and Dehalobium chlorocoercia strain DF-1, 11 can reductively metabolize PCBs into less toxic compounds, and the respective genes encoding reductive dehalogenases (RDases) have been identified. 9,12 However, the crystal structure of RDase catalyzing the dechlorination of PCBs has not been reported, enigmatizing the underlying mechanism and thus retarding the application of microbial reductive dechlorination in targeted bioremediation.…”
Section: Introductionmentioning
confidence: 99%